Partial Reconstitution of Factor VIII Activity from a Mild Crm+ Hemophilia A Patient by Replacement of the Defective A2 Domain - Pieneman, W. C.; Fay, P.; Briët, E.; Reitsma, P. H.; Bertina, R. M. (Thrombosis and Haemostasis, 1998)
We further characterised the abnormal factor VIII molecule (factor VIII Leiden) of a Crm+, mild hemophilia A patient with a factor VIII activity of 0.18 IU/ml and a factor VIII antigen of 0.95 IU/ml. Mutation analysis of the coding region, promoter and 3’ untranslated region of the factor VIII gene revealed the presence of a C to T substitution at codon 527. This nucleotide change predicts the replacement of an arginine to tryptophan in the A2 domain close to a suggested binding site for factor IXa. Since a previous study of this mutant factor VIII protein suggested that this protein had a reduced affinity for factor IXa, position 527 in the protein might be involved in the interaction with factor IXa.In this study we gathered evidence for our hypothesis that the Arg to Trp mutation at position 527 is the cause of the reduced activity of factor VIII Leiden. Replacement of the mutated A2 domain by wild type A2 domain partially corrected the defect.Factor VIII from normal and factor VIII Leiden plasma was concentrated by cryoprecipitation, activated with thrombin and incubated with excess wild type A2 domain. Competition with excess isolated human A2 domain resulted in a partial reconstitution of the factor VIIIa activity of thrombin treated factor VIII Leiden. This supports the hypothesis that the mutation in the A2 domain is the cause of the reduced factor VIII activity.